Intermittent Atrioventricular Block following Fingolimod Initiation - E. Gialafos; S. Gerakoulis; A. Grigoriou; V. Haina; C. Kilidireas; E. Stamboulis; E. Andreadou (Case Reports in Neurological Medicine)
A 47-year-old female patient with multiple sclerosis (MS) developed symptomatic intermittent 2nd degree atrioventricular block (AVB) of five-hour duration, five hours after the first two doses of fingolimod, that resolved completely. Frequency domain analysis of heart rate variability (HRV) revealed increased parasympathetic activity and decreased sympathetic tone, while modified Ewing tests were suggestive of impaired cardiac sympathetic function. We hypothesize that expression of this particular arrhythmia might be related to autonomic nervous system (ANS) dysfunction due to demyelinating lesions in the upper thoracic spinal cord, possibly augmented by the parasympathetic effect of the drug.